2015
DOI: 10.1093/gerona/glu314
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Insulin Improves Age-Related Cognitive Deficits and Reverses Electrophysiological Correlates of Brain Aging

Abstract: Peripheral insulin resistance is a key component of metabolic syndrome associated with obesity, dyslipidemia, hypertension, and type 2 diabetes. While the impact of insulin resistance is well recognized in the periphery, it is also becoming apparent in the brain. Recent studies suggest that insulin resistance may be a factor in brain aging and Alzheimer's disease (AD) whereby intranasal insulin therapy, which delivers insulin to the brain, improves cognition and memory in AD patients. Here, we tested a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 85 publications
11
71
2
Order By: Relevance
“…Indeed, there is evidence that insulin receptor numbers and their functions are decreased in aging and AD animal models (Zaia & Piantanelli, 1996; Frolich et al , 1998; Zhao et al , 2004; Zhao et al , 2008). At the cellular level, brain insulin deficiency and reduction in insulin signaling, perhaps mediated by insulin resistance, could represent one of the altered pathways linked to altered memory function or synaptic communication during aging and AD (Craft et al , 1996; Rasgon & Jarvik, 2004; de la Monte et al , 2006; Talbot et al , 2012; De Felice, 2013; Sasaoka et al , 2014; Maimaiti et al , 2016). One approach to combat this reduction in insulin signaling that has received much interest clinically is the use of intranasal insulin delivery to selectively increase insulin concentration in the brain (Born et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there is evidence that insulin receptor numbers and their functions are decreased in aging and AD animal models (Zaia & Piantanelli, 1996; Frolich et al , 1998; Zhao et al , 2004; Zhao et al , 2008). At the cellular level, brain insulin deficiency and reduction in insulin signaling, perhaps mediated by insulin resistance, could represent one of the altered pathways linked to altered memory function or synaptic communication during aging and AD (Craft et al , 1996; Rasgon & Jarvik, 2004; de la Monte et al , 2006; Talbot et al , 2012; De Felice, 2013; Sasaoka et al , 2014; Maimaiti et al , 2016). One approach to combat this reduction in insulin signaling that has received much interest clinically is the use of intranasal insulin delivery to selectively increase insulin concentration in the brain (Born et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The intranasal route of insulin administration raises insulin acutely in the central nervous system without much risk of peripheral hypoglycemia (Kern et al , 1999; Ott et al , 2014; Lochhead et al , 2015; Anderson et al , 2016; Maimaiti et al , 2016). Intranasal insulin therapy has been shown to improve memory function in AD patients and in healthy individuals (Benedict et al , 2004; Reger et al , 2006; Hanson & Frey, 2008; Reger et al , 2008; Craft et al , 2012; Schioth et al , 2012b; Freiherr et al , 2013; Craft et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin therapy in this study showed that even in sAD that insulin receptors are damaged, exogenous insulin administration seems to act effectively. Systemically administered insulin causes blood glucose changes so recently and in clinical trials, intranasal insulin is used to deliver insulin to the brain without affecting blood glucose [27][28][29][30]. The result of this study shows that icv administered insulin is protective in sAD animal model.…”
Section: Discussionmentioning
confidence: 68%
“…Besides, insulin triggers the clathrin-dependent endocytosis of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors, regulating the long-term depression [21] . A recent report indicates that the improved memory recall in rats after intranasal insulin administration may due to the amelioration of the age-related increase of Ca 2+ -dependent hippocampal after hyperpolarization, a well-characterized neurophysiological indicator of aging [23] . In AD, insulin action has been shown to decrease the burden of β-amyloid and hyperphosphorylation of tau, thus alleviate the pathological hallmarks (i. e., amyloid plaques and helical neurofibrillary tangles) [24] .…”
Section: Insulin Treatmentmentioning
confidence: 99%